Sosialisasi Prospek Karir di Industri IT Bagi Siswa SMK di Jakarta Selatan - Utomo; Fatimah, Titin; Ariesta, Atik; Farida Ariyani, Pipin (Artinara, 2022)
For vocational students, determining the choice of college majors according to their talents, interests, and abilities, which can determine future careers is a problem that is quite confusing and often occurs even until the time for college entrance selection arrives. Meanwhile, rapid technological innovation creates an IT industry that promises enormous career opportunities. Thus, vocational students need to know information about career prospects in the IT industry. This community service activity is carried out in the form of a webinar to provide information about careers in the IT industry and promising prospects in the future. The method used is the presentation of material online through the Zoom Meeting application to webinar participants who are vocational students in South Jakarta. The steps carried out in this activity are observation, data collection, literature review, material creation, implementation, and evaluation. The result of this activity is that vocational students get useful references and insights regarding career prospects in the IT industry.